திருமந்திரத்தில் தாவரவியல் / Botany in Thirumandhiram - அ. லீமா/A. Leema; Dr. M. Ashwini Krithika (Chenkaantal)
Devotional literature is one of the genres of literature that deals with spiritual concepts. In this, Saiva and Vaishnava literature is revered. The books written by the Saivite Nayanmars are called Thirumurais and the books written by the Vaishnava Alvars are called Nalayira Divya Prabandham. Tirumantra is the tenth of the twelve Saivite treatises. This book was written three thousand years ago by a Siddha named Thirumoolar. This Trimantra is the basic religious ideology of Saivism. Thirumoolar has beautifully expressed the concept of science at a time when science was not developed. Along with physics, music and Tamil, Science is seen in his works. Scientific matters are widely found in Saiva literature Tirumandhiram. Therefore, the article examines the concepts of botany found in Tirumandhiram.